Labour Market Effects of Eastern European Migration in Wales. (4th July 2013) - Lemos, Sara
<x xml:space="preserve">Abstract</x> The enlargement of the European Union in May 2004 triggered a relatively large and rapid migration inflow into Wales which was concentrated into narrow districts and occupations. We found little evidence that the inflow of migrants contributed to a fall in wages or a rise in claimant unemployment in Wales between 2004 and 2006. In particular, we found no evidence of an adverse impact on young, female or low‐skilled claimant unemployment and no evidence of an adverse impact on the wages of the low‐paid.